Student Video Project As A Means To Practice Constructivist Pedagogy In The Foreign Language Classroom - Nikitina, Larisa (Penerbit Universiti Sains Malaysia, 2009)
This article describes a video project in which learners of the Russian language at Universiti Malaysia Sabah (UMS) were involved in making their own digital video in the target language. The activity is viewed from the constructivist perspective of education, in which an active construction of knowledge by the learners, the social nature of learning, the authenticity of the learning situation, and the ability of the students to determine their own learning goals are prioritised. This paper gives a brief overview of two student-produced videos and reports the learners’ perceptions of the benefits of the project. It concludes that involving language learners in a video-making activity offers a feasible way to integrate technology into language curriculum and to infuse constructivist pedagogical strategies into foreign language teaching. Although this study was done in the context of Russian language teaching and learning, the activity described can be implemented with learners of various languages at different levels of proficiency.